2012
DOI: 10.2147/ijn.s28261
|View full text |Cite
|
Sign up to set email alerts
|

Increased brain radioactivity by intranasal 32P-labeled siRNA dendriplexes within in situ-forming mucoadhesive gels

Abstract: Background: Molecules taken up by olfactory and trigeminal nerve neurons directly access the brain by the nose-to-brain pathway. In situ-forming mucoadhesive gels would increase the residence time of intranasal material, favoring the nose-to-brain delivery. In this first approach, brain radioactivity after intranasal administration of 32 P-small interference RNA (siRNA) complexed with poly(amidoamine) G7 dendrimers (siRNA dendriplexes) within in situ-forming mucoadhesive gels, was determined. Materials:32 P-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 56 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…The intranasal delivery is a powerful, non-invasive method to directly deliver chemicals and peptides to the brain, which is not obstructed by the blood-brain barrier, avoids fast systemic clearance, and limits potential secondary effects. It has been used to deliver chemicals, peptides, oligonucleotides, proteins and stem cells into the brain (Cai et al, 2011; Cooper et al, 2013; Kim et al, 2012; Perez et al, 2012; Rat et al, 2011; van Velthoven et al, 2013; Yang et al, 2013a; Yang et al, 2013b). A recent study demonstrated that silencing miR-134 with intranasal administration of miR-134 antagomir LNA in each nostril produced neuroprotective and prolonged seizure-suppressive effects in mice (Jimenez-Mateos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The intranasal delivery is a powerful, non-invasive method to directly deliver chemicals and peptides to the brain, which is not obstructed by the blood-brain barrier, avoids fast systemic clearance, and limits potential secondary effects. It has been used to deliver chemicals, peptides, oligonucleotides, proteins and stem cells into the brain (Cai et al, 2011; Cooper et al, 2013; Kim et al, 2012; Perez et al, 2012; Rat et al, 2011; van Velthoven et al, 2013; Yang et al, 2013a; Yang et al, 2013b). A recent study demonstrated that silencing miR-134 with intranasal administration of miR-134 antagomir LNA in each nostril produced neuroprotective and prolonged seizure-suppressive effects in mice (Jimenez-Mateos et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The potential of mucoadhesive gel formulations was also displayed by Perez et al . [89]. They coupled radioactive siRNA to PAMAM dendrimers to form dendriplexes, and formulated these particles into mucoadhesive gels containing either 1% (w/w) chitosan or 0.25% (w/w) carbopol 974P NF TM .…”
Section: Improvement Of the Nose-to-brain Pathway Through Formulatmentioning
confidence: 99%
“…Another study by the same research group showed intranasal siRNA delivery against HMGB1 gene, using PAMAM dendrimer formulation to cause neuroprotection in the postischemic brains of Sprague-Dawley rats [ 52 ]. Another study showed the intranasal delivery of radioactive 32 P-siRNA dendriplexes complexed in mucoadhesive gels with maximum expression in the olfactory bulb [ 23 ]. These applications are in accordance to the study performed by our group, suggesting intranasal delivery is a well established route to deliver nanoparticle formulations targeting brain and causing a therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%